2007
DOI: 10.1007/s10461-007-9339-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring HIV-related Stigma Among Chinese Service Providers: Confirmatory Factor Analysis of a Multidimensional Scale

Abstract: An HIV-related stigma scale for health care workers needs to be multidimensional in that it should encompass attitudes that might be experienced by the general public about people living with HIV/ AIDS (PLWHA) (e.g., fear, shame, blame) and, further, specifically capture perceptions of appropriate professional care and medical responsibilities regarding PLWHA. A 17-item, 5-factor multidimensional HIV-related stigma scale was developed and validated using both exploratory and confirmatory factor analysis among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 33 publications
1
73
1
Order By: Relevance
“…A number of instruments designed to measure HIVrelated stigma in the general population and among special groups (e.g., healthcare workers) have been developed and validated in multiple languages (Genberg et al 2007;Kalichman et al 2005;Stein and Li 2007;Tanzania Stigma-Indicators Field Test Group 2005;Van Rie et al 2008;Zelaya et al 2007); however, no tool designed to measure HIV-related stigma specifically among persons living with HIV has yet, to the authors' knowledge, been validated and published in Spanish (Berger et al 2001;Holzemer et al 2007;Sayles et al 2008;Tanzania StigmaIndicators Field Test Group 2005;Visser et al 2008). In the United States, Hispanics represent nearly 20% of all people living with AIDS (Centers for Disease Control and Prevention 2007), and an estimated 1.7 million HIVinfected persons reside in Latin America (Joint United Nations Programme on HIV/AIDS (UNAIDS) and the World Health Organization (WHO) 2006), where Spanish is the predominant language.…”
Section: Introductionmentioning
confidence: 99%
“…A number of instruments designed to measure HIVrelated stigma in the general population and among special groups (e.g., healthcare workers) have been developed and validated in multiple languages (Genberg et al 2007;Kalichman et al 2005;Stein and Li 2007;Tanzania Stigma-Indicators Field Test Group 2005;Van Rie et al 2008;Zelaya et al 2007); however, no tool designed to measure HIV-related stigma specifically among persons living with HIV has yet, to the authors' knowledge, been validated and published in Spanish (Berger et al 2001;Holzemer et al 2007;Sayles et al 2008;Tanzania StigmaIndicators Field Test Group 2005;Visser et al 2008). In the United States, Hispanics represent nearly 20% of all people living with AIDS (Centers for Disease Control and Prevention 2007), and an estimated 1.7 million HIVinfected persons reside in Latin America (Joint United Nations Programme on HIV/AIDS (UNAIDS) and the World Health Organization (WHO) 2006), where Spanish is the predominant language.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on PLWH suggests that five stigma-related constructs-internalized shame, belief in good care, fear, prejudice, and stereotypesplay roles in physicians' intentions to discriminate against PLWH. 34,35 For example, prior research in Malaysia among medical and dental students showed greater intention to discriminate against PLWH to be associated with more negative attitudes toward PLWH, greater levels of HIV-related shame, 62 VIJAY ET AL.…”
Section: Stigma-related Correlates Of Discriminationmentioning
confidence: 99%
“…34 This scale has been previously used in the context of discrimination toward PLWH among medical and dental students in Malaysia 35 and healthcare providers in China. 34 We adapted the scale by substituting the term ''transgender patients'' for ''patients living with HIV/ AIDS'' for all items. The scale included four items, which participants rate on a Likert-type scale ranging from strongly disagree (1) to strongly agree (5).…”
Section: Intention To Discriminatementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been an increase in the literature on HIV-stigma, as the issue has gained visibility and greater conceptual clarity (Nyblade et al, 2013;Stein and Li 2008;Akanbi et al, 2010). A significant challenge to the success of achieving universal access to HIV prevention, treatment, care and support by 2010 is HIV-AIDS stigma and discrimination (Emmanuel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%